Sosialisasi Bahaya Bullying : Upaya Pencegahan, Dampak Beserta Sanksinya di SMAN 3 Cikarang Utara - Trias Saputra; Rahmiati Rahmiati; Ika Juhriati (CV. Ulil Albab Corp, 2024)
Bullying behavior is an issue that is often discussed nowadays. This behavior is often found in environments where it should not be, such as in schools and families. Bullying behavior is an aggressive or rude act that can cause conflict for the perpetrator and the victim. This community service activity is an outreach action that aims to provide education and prevent bullying to students at State High School (SMAN) 3 North Cikarang, so that they do not carry out bullying in the school environment or outside the school environment. The method used in this activity is providing material in the form of lectures and questions and answers. The results of the socialization activity show that students are very motivated in the activity process and can understand the material and information presented by the presenters. The implication of this activity is that students are aware of the negative impact of bullying behavior and are responsible for preventing this behavior in their daily environment